The DETERMINATION OF AMILORIDE VIA QUENCHED CONTINUOUS FLUORESCENCE OF AZO DYE USING LOW-PRESSURE MERCURY LAMP TUBE (UV-LIGHT) AND MULTI SOLAR CELLS AT 2 X 90° AS A DETECTORS - NAFEA, HUDA MUAYAD; TURKEY, NAGHAM S. (International Journal of Applied Pharmaceutics, 2020)
Objective: The aim of the method was to develop a novel, simple and rapid fluorometric method determination of Amiloride (AMD) in pure form and pharmaceutical drugs via fluorescence measurements. Methods: The method depends on fluorescence quenching of 2H-chromene azo dye (2-(4-nitrophenyl)-N-(4-(phenyldiazenyl)-2H-chromen-4-amine) upon adding Amiloride (AMD) using homemade ISNAG 2 X 90° multi solar cell via low-pressure mercury lamp at two significant wavelengths 184.9 and 253.7 nm combined with continuous flow injection analysis. Results: Under the optimized conditions, the fluorescence quenching linear working range and percentage linearity (r2%) was (0.03-8 mmol/l) and 98.78 %, respectively. The suggested method was effectively applied to the determination of AMD in two different pharmaceutical drugs and compared with the classical method (UV-vis spectrophotometry at λ=540 nm). Conclusion: The proposed and established method is simple, direct, and efficient. The statistical comparison results using a t-test at 95% confidence interval that was applied to compare the new and classical method showed there are no significant differences between the two methods.